Gamificação como elemento pedagógico: a integração entre ensino e a Abordagem STEAM na Educação Física - Farias, Iuri Nunes (2025)
The research addressed the coverage of the work that involved the use of gamification as a pedagogical element in supporting teaching and learning in the school environment with the STEAM (Science, Technology, Engineering, Arts and Mathematics) approach with interventions on the 9th grade class of the Final Years of Elementary School. Technology is seen as school challenge, however, we sought to understand the capabilities and benefits that gamification can bring to education. Its objective is to investigate how the mobilization established in gamification promotes the convergence of content in the area of Physical Education teaching, through the STEAM approach. To this end, the methodological proposal used action research in a rural school, in the interior of the state of Rio Grande do Sul. The research is of a qualitative and quantitative nature and presents the facts and phenomena existing in its activities. A board game was developed that involved the Arduino platform due to the technological aspects necessary in today's world, which are the school's responsibility to educate. This process integrated the pedagogical and educational practices present in the digital environment into the school environment, promoting autonomy and critical thinking in students about their citizenship and social contexts. The work was carried out in six phases: the first phase (what is gamification?); the second (what types of games and their characteristics?); the third (digital game and its transposition into a physical game); the fourth (new contact with digital games, seeking to extract their characteristics and possibilities with Physical Education); the fifth (construction and development of the board game); and the sixth phase (presentation of the game to the other classes in the school). Field reports were used as data collection instruments, due to the qualitative and ethnographic nature of the researcher in the field, and the MEEGA + KIDS questionnaire, which acted in the evaluation of the development of experiences and usability of the game, including the perception of learning, feelings and interactions with the environment and other players. The use of gamified environments with the STEAM approach has enabled students to learn and study in a more enjoyable and motivating way and has contributed greatly to the teaching of Physical Education content, as well as Arts and Geography subjects. The game has presented itself as a possibility to transcend the screen environment into the real world, where students are able to analyze the reality that manifests itself globally, constructing meanings and connecting what is learned at school with what is experienced outside of it.